Fretting corrosion behavior of WC-10Co-4Cr coating on Inconel 690 alloy by HVOF thermal spraying. (January 2023) - Yin, Meigui; Shao, Yixuan; Kang, Xiaofei; Long, Jiangqi; Zhang, Xiaofeng
Abstract: WC-10Co-4Cr coating was deposited through supersonic flame of high-velocity oxygen fuel (HVOF) process on the outside surface of Inconel 690 alloy tube. The fretting corrosion behavior of substrate- and coating- treated alloy tubes under dry state and seawater are compared. Results show remarkable differences between substrate- and coating-treated samples in electrochemical corrosion response and wear behavior. The fretting wear resistance of the WC-10Co-4Cr coating-sprayed alloy tube considerably improved because its surface mechanical properties are better than that of the substrate. Though the initial static corrosion performance of the coating is poorer than the substrate alloy tube, its excellent wear resistance helps decrease corrosion rate. In addition, the predominant damage mechanism of fretting corrosion was abrasive wear, fatigue delamination, and corrosion.